Long Covid-19, Radiological Findings, and Its Management: A Systematic Review - Soewondo, Widiastuti; Putro, Prasetyo Sarwono; Hermansah, Muhamad Lukman; Lestari, Lilik; Reviono, Reviono; Harsini, Harsini; Adhiputri, Artrien (Indonesian Journal of Medicine, 2021)
Background: COVID-19 is a disease caused by SARS-CoV-2 and has numerous clinical spectrums. Mild respiratory infection is the common clinical manifestation of COVID-19, and the less common is pneumonia accompanied by fever, cough, and breathing difficulty. Long COVID can be defined as prolonged signs and symptoms which cannot be explained for other reasons 4 weeks after being diagnosed with SARS-CoV-2. This study aimed to describe the cause of illness is confirmed or suspected COVID-19 patients, specifically on long COVID.Subjects and Method: We performed literature searches of the latest articles with Medline, CINAHL (EBSCO), Global Health (Ovid), WHO Global Research on COVID-19 database, LitCovid and Google Scholar databases published from 2019 to 2020. Two reviewers searched all articles independently (P and W, with 7 and 10 years of experience, respectively). We conducted a systematic review to provide recent evidence of symptoms and complications in long COVID. We followed PRISMA guidelines.Results: A total of 22 papers was identified and screened for eligibility from medical databases. There were 15 papers included in this review. Reason for the continuous symptoms covid an extent of organ destruction, continuous response of chronic inflammation or immunology reaction, non-specific effect of hospital admission, some critical disease, post ICU syndrome, complications from COVID-19 infection,  morbidities and adverse effects of medications used. Common symptoms are fatigue, shortness of breath, cough, chest pain, palpitations, dizziness, arthralgia, myalgia and weakness, sleep problems, sharp pain, gastrointestinal problems, rash and hair loss, impaired balance and ataxia, neurologic problems such as dementia, concentration disorders and poor quality of life.Conclusion: The incidence of long-term manifestations of COVID-19 has been increasing and systemic clinical symptoms affect many organs and systems. This can be due to numerous reasons like post-ICU syndrome, post-viral fatigue syndrome, permanent organ deterioration or others. Correspondence: Widiastuti Soewondo. Department of Radiology, Dr. Moewardi General Hospital/ Faculty of Medicine, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Indonesia. Email: widiastuti.sprad56@staff.uns.ac.idIndonesian Journal of Medicine (2021), 06(04): 387-392https://doi.org/10.26911/theijmed.2021.06.04.04